HUBUNGAN PENGETAHUAN, PENERAPAN SOP DAN PEMASANGAN SAFETY SIGN DENGAN KEJADIAN KECELAKAAN KERJA DI PROYEK APARTEMEN MAHATA MARGONDA - Matheos Karel; Catur Septiawan; Rosidi Roslan (Asosiasi Dosen Muda Indonesia, 2023)
The occurrence of work accidents is due to two main factors, namely environmental and mechanical factors or unsafe conditions and the second factor, namely human factors or unsafe actions. The purpose of this study was to determine the relationship between knowledge, SOP implementation and installation of safety signs with work accidents in the Mahata Margonda apartment project. This research method uses a quantitative method, based on its type using a cross sectional approach with a population of general workers in the construction of the Mahata Margonda apartment project. The results of this study show that from 70 respondents there were 27 (38.6%) general construction workers known to have had work accidents, 35 (50%) workers who had low knowledge, 40 (57.1%) workers with the implementation of SOPs that did not appropriate, 37 (52.9%) according to general workers the installation of safety signs is not appropriate. Based on the results of the chi square statistical test on the knowledge variable, the p-value was 0.001<(0.05), the application of SOP was obtained with a p-value of 0.023<(0.05), the safety sign installation was obtained with a p-value of 0.020<(0.05) which shows the results of a relationship between each variable and the incidence of work accidents. In conclusion, there are general workers who have experienced work accidents, general workers with low knowledge, inappropriate implementation of SOPs and inappropriate safety signs. There is a significant relationship between knowledge, application of SOP and installation of safety signs with the incidence of work accidents in the Mahata Margonda apartment project